Keratin 17 testing in pancreatic cancer needle aspiration biopsies predicts survival. Issue 11 (2nd June 2021) - Roa‐Peña, Lucia; Babu, Sruthi; Leiton, Cindy V.; Wu, Maoxin; Taboada, Sofia; Akalin, Ali; Buscaglia, Jonathan; Escobar‐Hoyos, Luisa F.; Shroyer, Kenneth R.
Abstract : Background: Although pancreatic ductal adenocarcinoma (PDAC) has one of the lowest 5‐year survival rates of all cancers, differences in survival exist between patients with clinically identical characteristics. The authors previously demonstrated that keratin 17 (K17) expression in PDAC, measured by RNA sequencing or immunohistochemistry (IHC), is an independent negative prognostic biomarker. Only 20% of cases are candidates for surgical resection, but most patients are diagnosed by needle aspiration biopsy (NAB). The aims of this study were to determine whether there was a correlation in K17 scores detected in matched NABs and surgical resection tissue sections and whether K17 IHC in NAB cell block specimens could be used as a negative prognostic biomarker in PDAC. Methods: K17 IHC was performed for a cohort of 70 patients who had matched NAB cell block and surgical resection samples to analyze the correlation of K17 expression levels. K17 IHC was also performed in cell blocks from discovery and validation cohorts. Kaplan‐Meier and Cox proportional hazards regression models were analyzed to determine survival differences in cases with different levels of K17 IHC expression. Results: K17 IHC expression correlated in matched NABs and resection tissues. NAB samples were classified as high for K17 when ≥80% of tumor cells showed strong (2+) staining. High‐K17 cases, including stage‐matched cases, had shorter survival. Conclusions: K17 has been identified as a robust and independent prognostic biomarker that stratifies clinical outcomes for cases that are diagnosed by NAB. Testing for K17 also has the potential to inform clinical decisions for optimization of chemotherapeutic interventions. Abstract : Keratin 17 (K17) expression, measured by immunohistochemistry (IHC), correlates in needle aspiration biopsies (NABs) and matched resected pancreatic ductal adenocarcinoma (PDAC) tissue sections. K17 IHC is a negative prognostic biomarker in PDAC NABs.